Tablet for two: How do children collaborate around single player tablet games?. Issue 145 (January 2021) - Fleck, Rowanne; Vasalou, Asimina; Stasinou, Konstantina
Highlights: Single player games/apps on tablets are used in collaborative configurations in the classroom. Tablets change the nature of coordination leading to more turn taking during collaborative episodes. When children approach the task as a co-constructed space, high quality collaborative discussion can occur. The design of the game learning task can promote, or inhibit effective collaborative discussion. Abstract: Tablet computers are increasingly used in school classrooms. However, despite the fact that these devices are conceived as single-user devices, and most games or apps developed for them are designed for single-users, pairs or groups of students usually use these devices. Surprisingly little research has been done to explore the ways in which these devices support or not children's collaboration – instead research has focused on larger tabletop computers, or on collaboration around configurations of multiple tablet computers. In this paper we present a case-study analysis of pairs of children playing single player tablet games together. We use a combination of temporal video analysis and the Collaborative Learning Mechanisms (CLM) framework previously developed to understand collaboration around surfaces. This analysis aims to unpack collaborative interactions around these devices and identify ways in which successful and less successful collaborations occur. A comparison of our findings to previous studies of interactions around larger tabletop surfaces reveals some of the ways interactions around tablets differ to these. We use these understandings to begin to outline some of the issues to take into consideration when facilitating and designing for children's collaboration around single tablet computers.